DISTRIBUTION OF LOBSTER LARVAE, HOMARUS AMERICANUS, AND ZOOPLANKTON PREY IN THE GULF OF MAINE AND GEORGES BANK STOCK AREA - Benfer, Caroline (My University, 2023)
The American lobster, Homarus americanus H. Milne-Edwards, 1837 is a valuable fishery subject to rapid warming of the Gulf of Maine (GOM) and Georges Bank (GBK). Data to address large-scale larval distribution are lacking due to the logistical challenge of sampling their hyperdispersed larvae. Our study has established seasonal abundance patterns of larvae and their prey in the GOM on an unprecedented spatial scale. We completed a season-long survey in partnership with industry and resource managers to quantify seasonal patterns of larval abundance at transects spanning approximately 300 km of coastline in 2021. We compared our data with historical surveys with respect to differences between inshore (5 km) and offshore (40 km), and between eastern and western hydrographic regions. We also examined spatial and temporal patterns in the abundance of zooplankton prey. The data collected significantly improves our understanding of larval dynamics in the Gulf of Maine, establishes a baseline for future studies, and will provide an opportunity to ground truth and calibrate models of larval transport.
Keywords: American lobster; Homarus americanus; Larvae distributions; Gulf of Maine; zooplankton